The Attitudes of Computer Science Students and Instructors on Academic Social Network (ASN) Site: Case of University of Sulaimani - Ahmed, Mohammed Abubakr (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Nowadays, Internet, specifically Social Network Sites (SNS) have a great influence on the education system and academic life in universities. The main purpose of this study was to find out and discover instructors’ and students' attitudes towards the use of both SNS and Academic Social Network (ASN) site in their academic life in university of Sulaimani. In addition, UoS_ASN site was proposed and developed as an ASN site. The development of UoS_ASN site was formulated by the design-based research approach. Later, it was tested and used by students and instructors in the same university then students’ and instructors' attitudes and opinions were examined. The core purpose of UoS_ASN site was to assemble instructors and students online which it gave opportunity to them to communicate and collaborate with each other, disseminate tutorials, research and academic papers as well as help them to express their ideas and opinions. In this research, both qualitative and quantitative research methods were administered. The semi-structure interview was used to collect qualitative data with the instructors and questionnaire tools were used to collect quantitative data with the students. The participants in this research consisted of 105 students and 11 instructors. The result of the research demonstrated that instructors and students mostly have a positive attitude toward the use of SNSs and UoS_ASN. Keywords: Social Network Sites, Academic Social Network, ICT, E-learning

ÖZ: Günümüzde internet, özellikle, Sosyal Ağ Siteleri (SNS), eğitim sistemi ve akademik yaşam üzerinde güçlü bir etkiye sahiptir. Bu araştırmanın amacı Sulaimani Üniversitesi'ndeki öğrencilerin ve akademisyenlerin, SNS ve Akademik Sosyal Ağ (ASN)’larla ilgili olarak, her ikisinin akademik hayatlarındaki rolüne yönelik görüşlerini tespit edip belirlemeyi amaçlamaktadır. Bu sebeple, UoS_ASN sitesi önerilmiş ve bir ASN sitesi meydana getirilmiştir. UoS_ASN sitesinin geliştirilmesi, tasarıma-dayalı araştırma yaklaşımı ile formüle edilmiştir. Daha sonra aynı üniversitede öğrenci ve öğretim görevlileri tarafından kullanılarak test edilmiş, akabinde tutum ve düşünceleri incelenmiştir. Bu sitenin amacı, öğretmenleri ve öğrencileri aktif olarak bir araya getirip, birbirleriyle iletişim kurup işbirliği yapmalarını, araştırma ve akademik makaleleri yaymayı ve nihayetinde fikir ve düşüncelerini ifade etmelerinde yardımcı olmayı sağlamaktır. Bu araştırmada hem nicel hem de nitel veri toplama yöntemleri kullanılmıştır. Öğretmenlerle nitel veri toplamaya dayalı yarı-yapılandırılmış görüşme, öğrencilerle ise niceliksel veri toplamaya dayalı anket kullanılmıştır. Araştırmaya toplamda 105 öğrenci ve 11 öğretim elemanı katılmıştır. Çalışmanın sonucunda öğrencilerin ve öğretmenlerin büyük bir çoğunluğunun, SNS'ler ve UoS_ASN’larin kullanımına karşı pozitif tutum sergiledikleri tespit edilmiştir. Anahtar Kelimeler: Sosyal Ağ Siteleri, ICT, Akademik Sosyal Ağ, E-Öğrenme
Master of Science in Information and Communication Technologies in Education. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Education, Dept. of Information and Communication Technologies in Education, 2018. Supervisor: Dr. Fatma Tansu Hocanın.
Keywords: Information and Communication Technologies in Education; Information and Communication Technologies in Education--University of Sulaimani--Iraq; Student Attitudes--Instructor Attitudes--Information Communication Technologies--Academic Social Network (ASN) Site--University of Sulaimani--Iraq; Education - Computer network resources; Educational Technology--E-Learning; Teaching--Computer Network Resources; Social Network Sites; Academic Social Network; ICT; E-learning; Attitude; Education; Information and Communication Technology